2013
DOI: 10.1007/s12105-013-0473-9
|View full text |Cite
|
Sign up to set email alerts
|

Schwannoma-Like Pleomorphic Adenoma: A Case Report with Review of the Literature

Abstract: Pleomorphic adenoma is a common benign salivary gland tumor, which represents about 66 % of benign neoplasms of the salivary glands. Although it can occur in any salivary gland, it is most frequently found in the parotid. Pleomorphic adenomas are renowned for their cytomorphological and architectural heterogeneity that are characterized by intermixed epithelial and mesenchymal-like components. We report a rare case of pleomorphic adenoma of the parotid gland with prevalent schwannoma-like features mimicking a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Further, this ambiguity is extended histopathologically when PAs show a divergent schwannoma-like phenotype as demonstrated in our case and previous reports [4][5][6][7][8]. Examples of epithelioid schwannomas of the parotid gland diagnosed as PAs have also been reported [31].…”
Section: And Present Case]supporting
confidence: 74%
See 4 more Smart Citations
“…Further, this ambiguity is extended histopathologically when PAs show a divergent schwannoma-like phenotype as demonstrated in our case and previous reports [4][5][6][7][8]. Examples of epithelioid schwannomas of the parotid gland diagnosed as PAs have also been reported [31].…”
Section: And Present Case]supporting
confidence: 74%
“…S100, a marker that is most useful in the diagnosis of a schwannoma finds no application in its differentiation from a schwannoma-like PA because S100 also stains myoepithelial cells [11,14]. Unlike previous two studies [7,8], AE1/AE3 pankeratin was not used in this case. A study by Fanburg-Smith et al showed that although 22 peripheral schwannomas examined were negative for AE1/AE3 pankeratin, 72/104 (69%) cases of retroperintoneal schwannomas were positive for AE1/AE3 [15].…”
Section: And Present Case]mentioning
confidence: 79%
See 3 more Smart Citations